A novel IgG Fc by computer-aided design enhances heavy-chain heterodimerization in bi- or trispecific antibodies. (1st August 2022) - Wang, Bo; Lin, Jun; Hoag, Matthew R; Wright, Meredith; Ma, Mingjun; Cai, Wenyan; Gallolu Kankanamalage, Sachith; Liu, Yue
Abstract: The classical `knob-into-holes' (KIH) strategy (knob(T366Y)/hole (Y407T)) has successfully enhanced the heterodimerization of a bispecific antibody (BsAb) resulting in heterodimer formation up to 92% of protein A (ProA)-purified protein pool. However, it does not show high efficiency for every BsAb. KIH was initially applied to a CD20/CD3 BsAb. After in silico modeling, two additional new mutations, S354Y in knob-heavy chain (HC) and Q347E in hole-HC, together with KIH named `ETYY', were introduced in the Fc. The CD20/CD3 BsAb hybrid only represented 50% of the ProA-purified protein pool when KIH was applied. With ETYY, the percentage of CD20/CD3 hybrid increased to 93.8%. CD20/CD3-v4b (containing ETYY) retains the original activity of the BsAb at both Fab and Fc regions, and also shows good developability. These results indicate that the computer-aided novel ETYY design has the potential to improve the development of next-generation BsAbs with higher yields and simpler purification. Abstract : Statement of Significance: The computationally designed novel ETYY mutations improve heterodimer formation in multi-specific antibodies while preserving the functional and physicochemical properties. This could greatly enhance the large-scale manufacturability and ease of purification for multi-specific antibodies for which heterodimerization is necessary.